Search
Ask a question
0

how do I solve the substitution equation as follows:y=-4x+5 y=-3x+4

Y=-4X+5
Y=-3X+4

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Heather G. | Math and Geosciences TutorMath and Geosciences Tutor
5.0 5.0 (7 lesson ratings) (7)
0
Here's a hint and one way of solving the problem (there are other methods too):
 
Since you have two equations that define what Y is, set them equal to each other and solve for X.  i.e. -4X+5 = -3X+4.  They should be equal to each other, as they both are equal to Y.
 
Once you get the value for X, you can plug that X value back into one of the equations (it doesn't matter which one) to solve for Y.
 
Good luck!